Works of Art, Produced from Concrete, Installed in Public Spaces from the 1950's to the 1980's in the former Czechoslovakia - Technologies and Surveys - Červinka, Josef (Polish Mineral Engineering Society, 2018)
The article discusses techniques applied to artworks created from concrete in the period from 1950 until 1989. The aim of submitted text is to broaden view on the surveyed objects as to their future repairs and restoration. In addition, the paper wishes to draw attention to topical issues of heritage preservation. The introduction highlights technological questions related to terminology. Surveys, characterizing a specific type of use of concrete material, including detected damage indicators, are introduced on examples of the selected concrete objects. The article follows topographic and archive survey of the mentioned artwork fund.
Umělecká díla z betonu vzniklá ve veřejném prostoru v období 50. - 80. let 20. století v bývalém Československu – technologie a průzkumy
Keywords: works of art; concrete; Czechoslovakia; umělecká díla; beton; Československo